The microbial nature of laminated limestones: Lessons from the Upper Aptian, Araripe Basin, Brazil - Catto, Bruno; Jahnert, Ricardo Jorge; Warren, Lucas Verissimo [UNESP]; Varejao, Filipe Giovanini [UNESP]; Assine, Mario Luis [UNESP] (Elsevier, 2016)
The Araripe Basin, located in northeastern Brazil, originated during the Gondwana continental break-up responsible for the opening of the South Atlantic during the Early Cretaceous. In the Araripe Basin, the post-rift Aptian sequence corresponds to the Santana Group, which is composed, in upward succession, of mostly clastic continental and rare carbonate layers of the Barbalha, Crato, Ipubi and Romualdo Formations. The laminated limestones of the Crato Formation were deposited in a lacustrine environment preceding the deposition of the Ipubi Formation evaporites. They are age-equivalent to the limestones of the pre-salt interval of the east coast of Brazil, which contains large petroleum reserves. The excellent preservation of its macrofossils has made the Crato Formation known worldwide as a Fossil LagerstÃ¤tte. The limestones are macroscopically homogeneous, and their deposition has been previously attributed to chemical precipitation. Although the carbonate laminites are macroscopically undifferentiated, mineralogical variations, microscopic texture and distinctive biotic aspects supported the characterization of four microfacies: planar laminated, crustiform, nodular and rhythmic. The microfacies analysis indicated a strong and pervasive biological activity in the Crato limestone morphogenesis. Organominerals precipitated by the metabolic action of cyanobacteria and/or sulfate-reducing bacteria and methanogenic-oxidizing archea are represented by calcite and pyrite. Calcified coccoid and filaments are common, furthermore, the presence of calcified biofilms composed of exopolymeric substances (EPS) is ubiquitous. The presence of amorphous organic matter (AOM) and gypsum, particularly in the rhythmic microfacies, indicates anoxic/dysoxic conditions and stressful environments during periods of drought and low lake levels which favored the development and preservation of microbial biofilms. Phytoclasts and miospores when present in the succession indicate an extrabasinal contribution during wetter periods, although the environment remained of very low energy. The evidence of microbial influence in the formation of the laminated limestones of the Crato Formation is of great importance for understanding the excellent preservation of the unit's fossils and for modeling the evolution of the Aptian carbonate sequences in Brazil.
Keywords: Araripe basin; EPS; Laminated limestones; Lower Cretaceous carbonate; Microbialites; Organomineralization